Peran Inovasi Teknologi dalam Meningkatkan Daya Saing Ekspor - Husnul Khowatim; Dies Nurhayati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
For Indonesia, exports have a strategic role as a supporter of the national economy. In addition to being a source of foreign exchange, exports also support job creation, expand the domestic market, and strengthen the domestic industrial structure. One of the root problems that hinders Indonesia's export competitiveness is the low level of innovation in the production and processing sectors. The literature study method or literature review is an analysis technique used to gain a comprehensive understanding of a particular topic by studying and evaluating existing literature, such as journals, books, reports, and other sources relevant to the research topic. In the literature study on the Role of Innovation in Increasing Export Competitiveness. the role of technological innovation in exports is increasingly important considering the structural challenges faced so far, such as low added value of export products, minimal adoption of technology, and weak integration between industry, research, and government policy. Technological innovation plays a strategic role in increasing Indonesia's export competitiveness in the global market.